Effects of exercise-based cardiac rehabilitation on cardiorespiratory fitness: A meta-analysis of UK studies. (15th October 2016) - Almodhy, Meshal; Ingle, Lee; Sandercock, Gavin R.
Abstract: Background: Exercise-based cardiac rehabilitation can promote meaningful improvements in cardiorespiratory fitness (fitness) but the magnitude of such improvements varies according to local characteristics of exercise programmes. We aimed to determine if cardiac rehabilitation (CR), as practised in the United Kingdom (UK), could promote meaningful changes in fitness and to identify programme characteristics which may moderate these changes. Methods: Electronic and manual searches to identify UK CR studies reporting fitness at baseline and follow up. Change in fitness (Δfitness) was expressed as mean difference (95% CI) and effect size ( ES ). A random effects model was used to calculate the mean estimate for change in Δfitness. Between-group heterogeneity was quantified ( Q ) and investigated using planned sub-group analyses. Results: We identified n  = 11 studies containing 16 patient groups ( n  = 1 578) which used the incremental shuttle walking test (ISWT) (distance walked) to assess fitness. The overall mean estimate for Δfitness showed a significant increase in distance walked ( ES  = 0.48, P  < 0.001), but this estimate was highly heterogeneous ( Q  = 77.1, P  < 0.001, I 2  = 81%). Sub-group analyses showed significantly greater ES ( Q  = 3.94, P  = 0.046) for Δfitness in patients prescribed n  > 12 exercise sessions compared with those receiving n  ≤ 12 sessions. Conclusion: We found significant increases in fitness (based on ISWT) in patients attending exercise-based CR in the UK. However, UK studies provide approximately one-third of the exercise "dose", and produce gains in fitness less than half the magnitude reported in international studies. Highlights: UK studies describing changes in cardiorespiratory fitness due to cardiac rehabilitation are reviewed. Meta-analysis of results shows modest increases in cardiorespiratory fitness compared to international studies. Between-study heterogeneity is explained by the number of exercise sessions prescribed. UK programmes prescribe fewer sessions than reported in international studies. A review of exercise prescription in UK cardiac rehabilitation centres is recommended.